A phase 2, randomized, double‐blind, placebo‐controlled study to evaluate the efficacy and safety of soticlestat as adjunctive therapy in pediatric patients with Dravet syndrome or Lennox–Gastaut syndrome (ELEKTRA). Issue 10 (4th August 2022) - Hahn, Cecil D.; Jiang, Yuwu; Villanueva, Vicente; Zolnowska, Marta; Arkilo, Dimitrios; Hsiao, Samuel; Asgharnejad, Mahnaz; Dlugos, Dennis
Abstract: Objective: Dravet syndrome (DS) and Lennox–Gastaut syndrome (LGS) are rare treatment‐resistant childhood epilepsies classed as developmental and epileptic encephalopathies. ELEKTRA investigated the efficacy and safety of soticlestat (TAK‐935) as adjunctive therapy in children with DS or LGS (NCT03650452). Methods: ELEKTRA was a phase 2, randomized, double‐blind, placebo‐controlled study of soticlestat (≤300 mg twice daily, weight‐adjusted) in children (aged 2–17 years) with DS, demonstrating three or more convulsive seizures/month, or with LGS, demonstrating four or more drop seizures/month at baseline. The 20‐week treatment period comprised an 8‐week dose‐optimization period and a 12‐week maintenance period. Efficacy endpoints included change from baseline in seizure frequency versus placebo. Safety assessments included incidence of treatment‐emergent adverse events (TEAEs). Results: ELEKTRA enrolled 141 participants; 126 (89%) completed the study. The modified intent‐to‐treat population included 139 participants who received one or more doses of study drug and had one or more efficacy assessments (DS, n = 51; LGS, n = 88). ELEKTRA achieved its primary endpoint: the combined soticlestat‐treated population demonstrated a placebo‐adjusted median reduction in seizure frequency of 30.21% during the maintenance period ( p = .0008, n = 139). During this period, placebo‐adjusted median reductions in convulsive and drop seizure frequencies of 50.00% ( p = .0002; patients with DS) and 17.08% ( p = .1160; patients with LGS), respectively, were observed. TEAE incidences were similar between the soticlestat (80.3%) and placebo (74.3%) groups and were mostly mild or moderate in severity. Serious TEAEs were reported by 15.5% and 18.6% of participants receiving soticlestat and placebo, respectively. TEAEs reported in soticlestat‐treated patients with ≥5% difference from placebo were lethargy and constipation. No deaths were reported. Significance: Soticlestat treatment resulted in statistically significant, clinically meaningful reductions from baseline in median seizure frequency (combined patient population) and in convulsive seizure frequency (DS cohort). Drop seizure frequency showed a nonstatistically significant numerical reduction in children with LGS. Soticlestat had a safety profile consistent with previous studies.